There is always something new emerging from Africa - Xyraphis, Apostolos (HAPSc Policy Briefs Series, 2020)
This paper focuses on the political and economic significance of Africa for a declining Europe, from a Greek vision and perspective. We argue that major ongoing developments (covid-19 included) and those perspectively announced pose dilemmas and the burden of engineering of choice, to decision-makers. As there are no country-level solutions that could be sufficient to address contemporary complex issues such as migration flows, pandemias, sustainable growth, climate change and multiple inequalities, we explore a possible new moral basis for future Euro-African coordination and collaboration.